Ancoragem extra-alveolar com mini-implantes: uma realidade promissora na ortodontia - SANTOS, Maike Douglas Silva (2019)
In the universe of dentistry, dental specialties are in constant transformation resulting from numerous researches on various subjects. In this scenario, in orthodontics, new devices appear capable of perfecting and simplifying treatments previously considered complex with surgical indication. The present study aims to present the characteristics, indications, location of insertion, advantages and disadvantages of extraalveolar miniimplants that have recently been proposed as a therapeutic alternative for several clinical cases. Because of the ease of installation, low cost, non-interference of the roots during treatment, among other advantages, these new mini-bolts represent a new reality in the orthodontic routine.